2009
DOI: 10.5253/078.097.0311
|View full text |Cite
|
Sign up to set email alerts
|

Collision Risk of Birds with Modern Large Wind Turbines

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 6 publications
1
41
0
3
Order By: Relevance
“…The radius of the search circle around the turbines (Table 1) was in most cases equal to the mast height × 1.1, as in Krijgsveld et al (2009) and Winkelman (1992), up to the mast height × 1.2 (rarely × 1.6) or the tip height of the turbines (=highest point of the moving blades). The systematic searches within the search area were performed by one person (the author) who walked in parallel line transects with a distance of 4-6 m between the lines depending on the type of vegetation.…”
Section: Mortality Ratementioning
confidence: 95%
“…The radius of the search circle around the turbines (Table 1) was in most cases equal to the mast height × 1.1, as in Krijgsveld et al (2009) and Winkelman (1992), up to the mast height × 1.2 (rarely × 1.6) or the tip height of the turbines (=highest point of the moving blades). The systematic searches within the search area were performed by one person (the author) who walked in parallel line transects with a distance of 4-6 m between the lines depending on the type of vegetation.…”
Section: Mortality Ratementioning
confidence: 95%
“…However, numbers of between 0.05-28 birds per turbine per year are commonly given although figures of over 60 birds per turbine per year have also been stated (Johnson et al 2002;Barrios & Rodríguez 2004;Hötker et al 2004;Everaert & Stienen 2007;de Lucas et al 2008;Drewitt & Langston 2008;Krijgsveld et al 2009;Winkelman et al 2008). This variation is strongly related to the flux (or flight intensity) through a wind farm area.…”
Section: Conflicts Between Wind Farms and Birdsmentioning
confidence: 99%
“…This variation is strongly related to the flux (or flight intensity) through a wind farm area. The higher the bird-flux (number of flights), the more collision victims can be expected (Krijgsveld et al 2009; collision rate = collision risk * flux). Some field studies have revealed that certain turbines within a wind farm have a higher risk for birds than others.…”
Section: Conflicts Between Wind Farms and Birdsmentioning
confidence: 99%
“…Заметим, что данные приводятся для периода 1980-1990-е годы и ветроустановок старого поколения (Fact Sheet, 2005;Smallwood, Thelander, 2005). Современные ветровые парки с турбинами более 1 МВт в меньшей степени влияют на птиц (Krijgsveld et al,2009;Gray , 2012;Горлов та ін., 2014с).…”
Section: результаты и обсуждениеunclassified